To Keto or Not to Keto? A Systematic Review of Randomized Controlled Trials Assessing the Effects of Ketogenic Therapy on Alzheimer Disease. Issue 6 (29th June 2020) - Grammatikopoulou, Maria G; Goulis, Dimitrios G; Gkiouras, Konstantinos; Theodoridis, Xenophon; Gkouskou, Kalliopi K; Evangeliou, Athanasios; Dardiotis, Efthimis; Bogdanos, Dimitrios P
ABSTRACT: Alzheimer disease (AD) is a global health concern with the majority of pharmacotherapy choices consisting of symptomatic treatment. Recently, ketogenic therapies have been tested in randomized controlled trials (RCTs), focusing on delaying disease progression and ameliorating cognitive function. The present systematic review aimed to aggregate the results of trials examining the effects of ketogenic therapy on patients with AD/mild cognitive impairment (MCI). A systematic search was conducted on PubMed, CENTRAL, clinicaltrials.gov, and gray literature for RCTs performed on adults, published in English until 1 April, 2019, assessing the effects of ketogenic therapy on MCI and/or AD compared against placebo, usual diet, or meals lacking ketogenic agents. Two researchers independently extracted data and assessed risk of bias with the Cochrane tool. A total of 10 RCTs were identified, fulfilling the inclusion criteria. Interventions were heterogeneous, acute or long term (45–180 d), including adherence to a ketogenic diet, intake of ready-to-consume drinks, medium-chain triglyceride (MCT) powder for drinks preparation, yoghurt enriched with MCTs, MCT capsules, and ketogenic formulas/meals. The use of ketoneurotherapeutics proved effective in improving general cognition using the Alzheimer's Disease Assessment Scale-Cognitive, in interventions of either duration. In addition, long-term ketogenic therapy improved episodic and secondary memory. Psychological health, executive ability, and attention were not improved. Increases in blood ketone concentrations were unanimous and correlated to the neurocognitive battery based on various tests. Cerebral ketone uptake and utilization were improved, as indicated by the global brain cerebral metabolic rate for ketones and [ 11 C] acetoacetate. Ketone concentrations and cognitive performance differed between APOE ε4(+) and APOE ε4(−) participants, indicating a delayed response among the former and an improved response among the latter. Although research on the subject is still in the early stages and highly heterogeneous in terms of study design, interventions, and outcome measures, ketogenic therapy appears promising in improving both acute and long-term cognition among patients with AD/MCI. This systematic review was registered at www.crd.york.ac.uk/prospero as CRD42019128311.